The relative frequency of common neuromuscular diagnoses in a reference center - Ana Cotta; Júlia Filardi Paim; Elmano Carvalho; Antonio Lopes da-Cunha-Júnior; Monica M. Navarro; Jaquelin Valicek; Miriam Melo Menezes; Simone Vilela Nunes; Rafael Xavier-Neto; Sidney Baptista Junior; Luciano Romero Lima; Reinaldo Issao Takata; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT The diagnostic procedure in neuromuscular patients is complex. Knowledge of the relative frequency of neuromuscular diseases within the investigated population is important to allow the neurologist to perform the most appropriate diagnostic tests. Objective: To report the relative frequency of common neuromuscular diagnoses in a reference center. Methods: A 17-year chart review of patients with suspicion of myopathy. Results: Among 3,412 examinations, 1,603 (46.98%) yielded confirmatory results: 782 (48.78%) underwent molecular studies, and 821 (51.21%) had muscle biopsies. The most frequent diagnoses were: dystrophinopathy 460 (28.70%), mitochondriopathy 330 (20.59%), spinal muscular atrophy 158 (9.86%), limb girdle muscular dystrophy 157 (9.79%), Steinert myotonic dystrophy 138 (8.61%), facioscapulohumeral muscular dystrophy 99 (6.17%), and other diagnoses 261 (16.28%). Conclusion: Using the presently-available diagnostic techniques in this service, a specific limb girdle muscular dystrophy subtype diagnosis was reached in 61% of the patients. A neuromuscular-appropriate diagnosis is important for genetic counseling, rehabilitation orientation, and early treatment of respiratory and cardiac complications.